Methods and techniques of professional training of beginner teachers. Comparative analysis - Rus, Mihaela; Sandu, Mihaela Luminita; Rosca, Geanina; Butoi, Angelica (Technium Social Sciences Journal, 2022)
The status, merits and importance of a profession in society are given by the level of qualification of the practitioners, but also by the skills and professionalism they demonstrate. In addition to these attributes there must also be motivation, perhaps it is the most important aspect of all those listed. The teaching profession also belongs to the category of professions that successfully fall under this rule. The performance of the educated requires thorough training and motivation from the teachers. That is why in order to have remarkable results in education, we need not only reforms, but also teachers trained from a theoretical point of view, but also from a practical point of view. In the teaching profession an important element is practical, because it highlights situations that are not found in books. Thus, the future teacher observes the problem situations in advance and is documented. Through practice, teachers are motivated to deepen the theoretical notions as well.